Penguatan kemampuan guru Sejarah di abad 21 melalui pelatihan penulisan sejarah publik untuk guru MGMP Sejarah di Kabupaten Boyolali - Nanda Julian Utama; Syaiful Amin; Nugroho Bayu Wijanarko; Junaidi Fery Lusianto; Muhammad Hastya Refanza; Nur Dhuha Indah Paramesty; Nathanael Agung Kristanto (Universitas Negeri Malang, 2022)
The ability of 21st century teachers is a necessity that must be mastered by educators in order to be able to compete. Mastery of technology and various applications and the ability of teachers to conduct research must also develop so that there is no big gap between teachers and students in technology matters. In the field of history, the development of public history is an opportunity for teachers to develop a history learning base that refers to technology. In public history, a historian in this regard is a teacher who is free to explore a historical theme and present it as interestingly as possible. This training regarding the introduction and application of public history will be carried out in the environment of teachers in the History of Boyolali District Teachers' Meetings (MGMP). The purpose of this training is so that teachers understand what public history is, how it relates to learning in schools, and how to be actively involved in the development of history both based on education and for the community. Kemampuan Guru Abad 21 merupakan sebuah keniscayaan yang harus dikuasai oleh para pendidik agar mampu bersaing. Penguasaan teknologi dan berbagai aplikasi dan kemampuan guru dalam melakukan riset harus berkembang pula agar tidak terjadi gap yang jauh antara guru dan siswa dalam urusan teknologi. Dalam bidang sejarah, pengembangan sejarah publik menjadi sebuah peluang bagi guru untuk mengembangkan basis pembelajaran sejarah yang mengacu pada teknologi. Dalam sejarah publik juga seorang sejarawan dalam kaitan ini adalah guru bebas mengeksplor sebuah tema sejarah dan menyajikannya semenarik mungkin. Pelatihan ini mengenai pengenalan dan pengaplikasian sejarah publik ini akan dilakukan dilingkungan para guru dalam Musyawarah Guru Mata Pelajaran (MGMP) Sejarah Kabupaten Boyolali. Tujuan diadakan pelatihan ini agar para guru memahami apa itu sejarah publik, bagaimana hubungannya dengan pembelajaran di sekolah, dan bagaimana terlibat aktif dalam pengembangan sejarah baik yang berbasis Pendidikan maupun untuk masyarakat.